2005
DOI: 10.1111/j.1467-9965.2005.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean–variance Portfolio Choice: Quadratic Partial Hedging

Abstract: In this paper we investigate the problem of mean-variance portfolio choice with bankruptcy prohibition. For incomplete markets with continuous assets' price processes and for complete markets, it is shown that the mean-variance efficient portfolios can be expressed as the optimal strategies of partial hedging for quadratic loss function. Thus, mean-variance portfolio choice, in these cases, can be viewed as expected utility maximization with non-negative marginal utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…For incomplete markets with continuous assets' price processes and for complete markets, Xia [3] showed that Problem (1.2) is equivalent to the following optimization problem…”
Section: Self-financing Strategy (X H) Is Given Bymentioning
confidence: 99%
See 3 more Smart Citations
“…For incomplete markets with continuous assets' price processes and for complete markets, Xia [3] showed that Problem (1.2) is equivalent to the following optimization problem…”
Section: Self-financing Strategy (X H) Is Given Bymentioning
confidence: 99%
“…Isn't the Markowitz mean-variance portfolio selection theory reasonable? Xia [3] showed that for incomplete markets with continuous assets' price processes and for complete markets, the mean-variance efficient portfolios can be viewed as those of expected utility maximization with non-negative marginal utility. Now we present the main results of Xia [3] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well-known that optimizing expected quadratic utility yields a solution to the MV problem, see e.g. Xia (2005). However, quadratic utility generates a negative marginal utility for relatively large levels of wealth and thereby violates the classical assumption of strict monotonicity of the utility function.…”
mentioning
confidence: 99%